Characterization of the contribution of road deposited sediments to the contamination of the close marine environment with trace metals: Case of the port city of Busan (South Korea). (December 2020) - Jeong, Hyeryeong; Choi, Jin Young; Lim, Jaesoo; Shim, Won Joon; Kim, Young Ok; Ra, Kongtae
Abstract: We examined the concentrations of 12 trace metals in road-deposited sediments (RDS) and their contributions to the pollution of harbor/marine sediments in the port city of Busan, South Korea. The concentrations of Cr, Cu, Zn, Cd, Sn, Sb, and Pb in RDS affected by industrial and traffic activities were 6.7–25.7 times higher than those in marine sediments. The enrichment factors indicate that RDS are extremely polluted with Sb and moderately to strongly polluted with Cr, Cu, As, Sn, Pb, Zn, and Cd. The mean modified pollution index distinguished between unpolluted marine sediments, moderately to heavily polluted harbor sediments, and severely polluted RDS. Furthermore, harbor/marine sediments close to shipyards and the mouths of streams and rivers were found to be moderately polluted with Cu, Zn, Cd, Sb, and Pb. RDS containing trace metals accumulate on impervious surfaces and flow into the marine environment via untreated stormwater runoff. Graphical abstract: Unlabelled Image Highlights: Trace metals in marine sediments and road-deposited sediments (RDS) were studied. Metal pollution assessment was conducted in major port city (Busan) of South Korea. For RDS, enrichment factor (EF) results showed extremely polluted level with Sb. Urban runoff of RDS may be a potential pollution source for marine environments.